The Challenges in Application of ‘Cradle-to-Cradle Concept in Waste Management - Abd Ghaffar, Nurfarhanah Aqilah; Zainun, Noor Yasmin (Recent Trends in Civil Engineering and Built Environment, 2024)
The concept of ‘Cradle-to-Cradle’ (C2C) was an innovative design framework to achieve positive ecology impacts by improving the quality of products and services. C2C in waste management was one of the alternative techniques to avoid waste, develop newer production and processing techniques that can be used for other activities in the future. The objectives of this study were to identify the challenges and propose solutions for the challenges in the application of the concept in waste management. There are 13 challenges that were determined by gathering the information from the literature review and used to design the questionnaire. The quantitative data will be collected by using the Likert Scale. Taro Yamane formula was used to determine the sample size for finite population and Cronbach’s Alpha method was used to determine the reliability and acceptance of analysis. To analyze the data from the questionnaire, Principal Component Analysis (PCA) adopted from SPSS software was conducted to reduce and minimize information loss. From the PCA result, critical challenges of implementation of the C2C concept in waste management was determined according to principal component 1,2, and 3 which have eigenvalue more than 1, and it is used for further analysis. Therefore, there are 5 critical challenges were determined which are; (1) attitude and culture of Malaysians; (2) level of education and exposure to C2C concept; (3) lack of technical expertise in operating and applying C2C concept; (4) acts and regulations related to waste management been implemented well and suitable; and (5) excuses from industries to implement C2C concept. Thus, 5 critical challenges in the application of the C2C concept had been identified and solutions in applying this concept were determined can help in the implementation of this concept in Malaysia will be successful.